Time of day and endovascular treatment decision in acute stroke with relative endovascular treatment indication: insights from UNMASK EVT international survey. (8th July 2019) - Ospel, Johanna Maria; Kashani, Nima; Goyal, Mayank; Menon, Bijoy K; Campbell, Bruce C V; Fischer, Urs; Turjman, Francis; Mitchell, Peter; Yoshimura, Shinichi; Podlasek, Anna; Rabinstein, Alejandro A; Wilson, Alexis T; et al.
Abstract : Background and purpose: The decision to proceed with endovascular thrombectomy should ideally be made independent of inconvenience factors, such as daytime. We assessed the influence of patient presentation time on endovascular therapy decision making under current local resources and assumed ideal conditions in acute ischemic stroke with level 2B evidence for endovascular treatment. Methods and materials: In an international cross sectional survey, 607 stroke physicians from 38 countries were asked to give their treatment decisions to 10 out of 22 randomly assigned case scenarios. Eleven scenarios had level 2B evidence for endovascular treatment: 7 daytime scenarios (7:00 am–5:00 pm) and four night time cases (5:01 pm– 6:59 am). Participants provided their treatment approach assuming (A) there were no practice constraints and (B) under their current local resources. Endovascular treatment decisions in the 11 scenarios were analyzed according to presentation time with adjustment for patient and physician characteristics. Results: Participants selected endovascular therapy in 74.2% under assumed ideal conditions, and 70.7% under their current local resources of night time scenarios, and in 67.2% and 63.8% of daytime scenarios. Night time presentation did not increase the probability of a treatment decision against endovascular therapy under current local resources or assumed ideal conditions. Conclusion: Presentation time did not influence endovascular treatment decision making in stroke patients in this international survey.